Eleocharis maculosa (Cyperaceae), a new record for La Pampa province, Argentina (Semiárida, 2018)
Eleocharis maculosa (Vahl) Roem. & Schult. (Cyperaceae) is recorded for first time for La Pampa province. Geographic origin, life form and environment are briefly described. A key to differentiate it from the other species that grow in this province is given.
Keywords: New record; Cyperaceae; Eleocharis maculosa; La Pampa; Flora.